A concise encyclopedia of the philosophy of religion - Thiselton, Anthony C. (Oneworld, 2002)
Covering thinkers from Plato to Freud, offering detailed explanations of key themes such as evil, and outlining clear definitions of complex ideas like'the doctrine of analogy,' this is a comprehensive reference tool for all those studying, or interested in, the philosophy of religion.